2021
DOI: 10.1155/2021/1131280
|View full text |Cite
|
Sign up to set email alerts
|

Paving Plant‐Food‐Derived Bioactives as Effective Therapeutic Agents in Autism Spectrum Disorder

Abstract: Autism spectrum disorder (ASD) is a neurodevelopmental disorder, where social and communication deficits and repetitive behaviors are present. Plant-derived bioactives have shown promising results in the treatment of autism. In this sense, this review is aimed at providing a careful view on the use of plant-derived bioactive molecules for the treatment of autism. Among the plethora of bioactives, curcumin, luteolin, and resveratrol have revealed excellent neuroprotective effects and can be effectively used in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 186 publications
0
4
0
Order By: Relevance
“…Piperine, an alkaloid obtained from Piper longum L. and Piper nigrum L. (black pepper), possesses anxiolytic, neuroprotective, and cognition-enhancing effects [ 36 ]. Investigations conducted by Pragnya et al have revealed improved motor deficits in ASD murine models.…”
Section: Phytoconstituents In Asdmentioning
confidence: 99%
See 1 more Smart Citation
“…Piperine, an alkaloid obtained from Piper longum L. and Piper nigrum L. (black pepper), possesses anxiolytic, neuroprotective, and cognition-enhancing effects [ 36 ]. Investigations conducted by Pragnya et al have revealed improved motor deficits in ASD murine models.…”
Section: Phytoconstituents In Asdmentioning
confidence: 99%
“…Traditional medicine has been commonly used in the treatment of ASD. Plant bioactive constituents with neuroprotective actions have therapeutic potential in the treatment of neuropsychological disorders [ 35 , 36 ]. This review discusses the amassing literatures on ASD, predominantly focusing on the dysregulation of PI3K/Akt/mTOR signaling cascade as well as the genetic alteration of the pathway components in the development of ASD.…”
Section: Introductionmentioning
confidence: 99%
“…So, it not surprising that several studies found a connection between dietary deficiencies and ASD, as a consequence. To help ASD individuals, several plant-based bioactive compounds have been studied as a complement to ASD therapy [ 42 , 43 ].…”
Section: Bioactive Compounds From Plants As Antioxidant Anti-inflamma...mentioning
confidence: 99%
“…It has been suggested that gut microbiota imbalance and intestinal brain dysfunction, is more prevalent in ASD which seems to be modified by both foods and food products such as probiotics, herbal or natural ingredients including honeybee [8]. The purpose of this ingredients which can be used in industry or added to food products is modification immune system function, nervous system and endocrine system both directly or indirectly [9].…”
Section: Issn: 2577-4182mentioning
confidence: 99%